Inovasi Pelayanan Publik melalui penerapan Sistem Elektronik Surat Keterangan (E-SUKET) di Kota Kediri - Ahmada Reza Fajar Dwi Leksmana; Krishno Hadi; Asep Nurjaman (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2020)
Public services become the main face of the government as a bureaucratic organizer, poor public services from the government will get negative views from the public. The Office of Information and Communication of the City of Kediri as one of the government agencies implements the E-Suket (Electronic Certificate) as an innovation that was sparked to answer the problems of public services that exist in the people of the City of Kediri. The method used is descriptive qualitative method, the research subjects were conducted with the Kediri City Community and the Head of the Communication and Information Resources Development Division of the City of Kediri Communication and Information Office. Basuki Rahmat No. 15, Pocanan, Kediri City. Public service innovation E-Suket (Electronic Certificate) is an increase in public services in the City of Kediri, the change of public services from a manual system to an online service system. The existence of E-Suket as an innovation of the City Government of Kediri has not been able to overcome the existing problems, the problem is in the human resources sector in the field of informatics engineering for application administration in each village, the need for improvement and supervision of the system by the City Government of Kediri in order to provide the citizens of the City of Kediri smooth access in submitting applications application for letter through E-Suket.